Video learning for hearing impaired students through Massive Open Online Courses (MOOC) / Zainuddin Ibrahim - Ibrahim, Zainuddin (UiTM Press, 2020)
Learning for students with hearing loss needs to have several criteria for them to learn effectively. Although various learning methods for these students are available, they are only available in specific courses. The video approach to learning for students with hearing loss has a positive effect. However, studies on the effectiveness of elements that should be present in video content should be emphasized. The purpose of this study is to identify the criteria that should be included in the production of Learning disabilities video for MOOC platforms. The semi-structured interview method was applied to five video specialists and hearing aids. The description of the analysis shows that video learning for students with hearing loss needs to have a language translator for each content.